Mechanochemical synthesis of the copper autunites—a new route to remediation of potentially toxic elements - Kirk, CA; MacIver-Jones, FM; Wu, C; Johnson, B (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
This paper focusses on the potentially toxic elements (PTE), uranium (U) and arsenic (As), which are both of concern in many developing nations that have active mining histories. U and As are toxic and carcinogenic, with U also being radioactive. In some ex-mining sites where these two contaminants co-exist (e.g., at the South Terras Mine, UK and the Zoige deposit, China) the untreated mine tailings have weathered and formed secondary mineral phases such as metatorbernite (Cu(UO2)2(PO4)2.8H2O) and metazeunerite (Cu(UO2)2(AsO4)2.8H2O). These minerals (part of the autunite group) are highly stable phases, and their formation has thus acted as a natural remediation solution and prevented U and As contamination from migrating through the surrounding environment. In this research, we describe a novel method for the synthesis of metatorbernite and metazeunerite from laboratory reagents, which we suggest could be a promising treatment method for U- and As-containing mining wastes. The method we describe uses mechanochemical techniques, which eliminate the need for a solvent and is compatible with existing infrastructure in the mining industry (e.g. grinding and milling facilities). We discuss the method development and directions for future work, highlighting that the successful development of this technique could have significant societal impacts, particularly in developing regions with poor waste management. Our ultimate aim is to develop a sustainable remediation strategy that can be easily scaled up and applied to other hazardous solid wastes to markedly reduce latent environmental and health risks.
Keywords: remediation